ANALISIS PENGUATAN EKONOMI HALAL SEBAGAI PILAR UTAMA DALAM PENINGKATAN KINERJA UKM SEKTOR HALAL - Dura, Justita; Bukhori, Mohammad; Octaviola Rosanti, Nabila (RISTANSI: Riset Akuntansi, 2025)
This study aims to analyze the factors influencing halal sector SMEs in Indonesia in adopting halal certification, as well as to formulate strategies for strengthening the halal ecosystem. A purposive sampling technique was used to select 120 halal SMEs in Malang City as the sample. A mixed-methods approach was employed, combining Structural Equation Modeling-Partial Least Squares (SEM-PLS) to examine SME owners' behavior toward halal certification and Analytic Network Process (ANP) to develop strategies for strengthening the halal ecosystem. The findings indicate that understanding business value chains and applying subjective Islamic standards play a crucial role in driving the halal certification process. However, there remains room for improvement, particularly in education and understanding of the certification process. The study concludes that enhancing literacy and implementing adaptive policies that respond to SME needs are essential to strengthening and developing a sustainable halal economic ecosystem in Indonesia.